Chemical constituents from Ligularia purdomii (Turrill) Chittenden. (June 2017) - Wang, Yan-Ming; Zhao, Jian-Qiang; Yang, Jun-Li; Tao, Yan-Duo; Mei, Li-Juan; Shi, Yan-Ping
Abstract: The first phytochemical investigation on the roots of Ligularia purdomii led to the isolation and identification of 18 compounds, including two eremophilane sesquiterpenoids (1 and2 ), three benzofuran derivatives (3 –5 ), a triterpenoid (6 ), two steroids (7 and8 ), nine phenolic components (9 –17 ), and a monofatty glyceride (18 ). The structural elucidation of the isolated compounds was performed by spectroscopic data and comparison with the literature. Compounds (−)-syringaresinol (11 ), scopoletin (13 ), 3, 5-dimethoxy-4-hydroxy-benzaldehyde (14 ), and glycerol monolinoleate (18 ) have not been recorded in Ligularia genus previously. The chemotaxonomic significance of these isolated compounds has been summarized. Highlights: First phytochemical investigation on L. purdomii. 18 compounds were identified from the acetone extract of L. purdomii. Four compounds were reported from the genus Ligularia for the first time. The results had important significance for chemotaxonomy of L. purdomii.